IMMU-21. TARGETING EGFR IN HYPOMUTATED PEDIATRIC BRAIN TUMORS USING THE D2C7 IMMUNOTOXIN. Issue 2 (22nd June 2018) - Landi, Daniel; Thompson, Eric; McLendon, Roger; Desjardins, Annick; Chandramohan, Vidya; Ashley, David; Bigner, Darell
Abstract: BACKGROUND: EGFR is a receptor tyrosine kinase that is hyperactivated or overexpressed in many human cancers. Compared with brain tumors in adults, pediatric tumors harbor few somatic mutations, which reduces the antigenic burden and number of potential molecular targets. Compared to checkpoint agents, therapies that elicit innate-based, inflammatory immune responses appear better able to counter tumor-inherent immunosuppression and instigate adaptive antitumor immunity. D2C7-IT is a dual-specific antibody fragment that has a high affinity for both EGFRwt and EGFRvIII-expressing cells fused to a genetically engineered form of the Pseudomonas exotoxin. D2C7-IT has been used to treat 35 adults with malignant glioma on a phase I trial at Duke. D2C7-IT is well-tolerated and preliminarily appears to prolong survival in some patients. METHODS: We have tested five samples each from several primary pediatric tumor types and found marked, often diffuse EGFRwt overexpression in ependymoma, oligodendroglioma, malignant glioma, low-grade glioma, and pleomorphic xanthoastrocytoma. Because of this data and the potential that D2C7-IT will be even more effective against pediatric tumors with a lower tumor mutational burden (TMB), we are evaluating D2C7-IT delivered by intratumoral infusion in children with any of the above relapsed tumors in a phase I trial. CONCLUSIONS: As the primary objective, this study will establish the safety and feasibility of D2C7-IT treatment in children with an EGFRwt-expressing brain tumor. As exploratory objectives, we are assessing the pre-treatment TMB in these pediatric brain tumors and its impact on response to D2C7-IT treatment.